Program Mengajar Mengaji, Bakti Sosial dan Juga Festival Anak Sholeh di Desa Mamampang, Kecamatan Tombolopao Kabupaten Gowa - Pahmi, Sahyul; Irawan, Alfikri; Yusriadi, St Nurhikmah; Faizah, Nur; Hernisah, Nur; Faharuddin, Faharuddin; Karadona, Rosika Indri (Anotero Lembaga Scientific Pekanbaru, 2025)
This Community Service Program aims to increase access to religious education, strengthen social solidarity, and build religious awareness in Mamampang Village, Kunciopao District. This program includes three main activities: Teaching the Koran, Social Service, and the Shalih Children's Festival. The method used is Participatory Action Research (PAR), which emphasizes the active involvement of the community in every stage of implementation. Initial observations show that there are still limitations in the Koran teaching staff and a lack of religious activities involving children and teenagers. The results of this program show an increase in children's ability to read the Koran, active community involvement in social service, and high enthusiasm for the Shalih Children's Festival. This activity not only has a direct impact on the community, but also creates synergy between students and residents in an effort to improve the quality of religious education and social life in the village.